Pemanfaatan Aplikasi Quizlet pada Minat Belajar Siswa Kelas 3 SDIT DARUSSALAM - Fitri; Janattaka Janattaka (Arus Jurnal Pendidikan, 2022)
This study aims to describe the results of using the Quizlet application on the learning interest of 3rd grade students of SDIT DARUSSALAM. The use of the Quizlet application can be used to foster student interest in learning. The use of the Quizlet application un the learning process by using interesting features can make students feel happy to learn. This study uses qualitative methods and uses a descriptive approach. This research was conducted at SDIT DARUSSALAM Kampungdalem, Tulungagung Regency. The sample fot the study used grade 3 with a total of 23 students. The stages of implementing this research are the pre-field stage, the field work stage, the data analysis stage, and the completion stage. Data collection techniques in this study used observation, interviews for teachers and students, and documentation. The results of this study indicate that the learning process using the Quizlet application can increase students interest in learning. The use of the learning Quizlet application becomes more fun and does not make students bored quickly. So that they feel happy when learning using Quizlet.